Home-Based Resistance Training Terhadap Nyeri dan Fungsi Fisik Pada Osteoarthritis Lutut - Rangga Raditya Priatama; Iman Santoso (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Knee osteoarthritis is a global health issue with increasing prevalence, particularly among the elderly population. This condition is characterized by primary symptoms such as joint pain, stiffness, and reduced physical function, which significantly limit the patient's daily activities. One promising non-pharmacological approach to managing knee osteoarthritis is Home-Based Resistance Training (HBRT). HBRT combines the effectiveness of resistance training with the convenience of being performed at home and is increasingly supported by advancements in telerehabilitation technology. This study is a systematic review conducted based on the PRISMA-P guidelines, with literature searches from PubMed, Scopus, Semantic Scholar, Google Scholar, and Cochrane databases. The included articles were English-language publications from 2019 to 2024 that evaluated the effectiveness of HBRT in patients with knee osteoarthritis. The findings indicate that HBRT is significantly effective in reducing joint pain, with a decrease in WOMAC scores ranging from 24.78% to 29.64% (p < 0.001), and improving physical function by 21.54% to 30.2%. These improvements meet the Minimum Clinically Important Difference (MCID) criteria, indicating clinically significant benefits. Furthermore, the effectiveness of HBRT is comparable to machine-based training, particularly in patients with high baseline severity. With standardized exercise protocols and adequate technological support, HBRT can be considered a feasible and effective intervention strategy in the rehabilitation of knee osteoarthritis patients, especially in the digital era and in contexts where access to conventional healthcare facilities is limited.